MOTIVASI PENGEMBANGAN ILMU PENGETAHUAN DALAM PERSPEKTIF HADIS NABI - Ahmad Darlis (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2017)
This paper parse comprehensive information about the motivation of the development of science in the perspective of Hadith. Demanding and develop knowledge, 'ulum al-din or 'ulum al-dunya is a mandatory command (faridhah) in the hadith of the prophet. The mastery of both types of science will realize the happiness of the world and the hereafter simultaneously. Therefore, the hadith explains high motivation in this activity. For people who demand and develop science equated God with those who strive. Even their recompense is eternal paradise. In Islam, the development of science simply is not worth anything when it is not able to provide repair of the world and the hereafter. Therefore, the integration of science and charity faith is a necessity that must be integrated. Thus, Allah will raise the degree of the learned and faithful to some degree.